Collateral requirements for SME loans: empirical evidence from the Visegrad countries - Rahman, Ashiqur; Belas, Jaroslav; Kliestik, Tomas; Tyll, Ladislav (Journal of Business Economics and Management, 2017)
The purpose of this paper is to examine the determinants of collateral for small and medium enterprises (smes) in the context of Visegrad countries: Czech Republic, Slovak Republic, Hungary and Poland. The data set for this paper was obtained from the Business Environment and Enterprise Performance Survey (BEEPS), which was conducted by the World Bank and the European Bank for Reconstruction and Development (EBRD) from 2012–2014. A binary logistic regression model with different specifications was employed to examine the effect of independent variables on the incidence of collateral. The results show that risky borrowers need to pledge collateral and the reduction of asymmetric information can lower the incidence of collateral for smes. Moreover, we find that female borrowers are more likely to pledge collateral than male borrowers are. The results also suggest that loans with a longer maturity are more likely to be collateralized than short-term loans. We find evidence that bank-borrower proximity can alleviate the incidence of collateral whereas bank concentration may increase collateral requirements. Policy makers may consider these results to implement policies that can promote bank competition and can lower collateral requirements for female borrowers. The paper contributes to the ongoing debate on the determinants of collateral.